2013
DOI: 10.5194/se-4-387-2013
|View full text |Cite
|
Sign up to set email alerts
|

Crustal 3-D geometry of the Kristineberg area (Sweden) with implications on VMS deposits

Abstract: Abstract. Structural analysis of the Palaeoproterozoic volcanogenic massive sulfide (VMS) hosting Kristineberg area, Sweden, constrained by existing magnetotelluric (MT) and seismic reflection data, reveals that the complex geometry characterized by non-cylindrical antiformal structures is due to transpression along the termination of a major high-strain zone. Similar orientations of the host rock deformation fabrics and the VMS ore lenses indicate that the present-day geometry of the complex VMS deposits in t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
21
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(22 citation statements)
references
References 27 publications
1
21
0
Order By: Relevance
“…These metasedimentary rocks are expected to be conductive due to their high content of graphitic metapelites. The fact that the basement is found deeper in our current study area (about 10 km) than in the western part of the district (4 km, see Hübert et al, 2013) is in good alignment with the proposed crustal detachment by Skyttä et al (2013), shown in Figure 1.…”
Section: Large Conductorssupporting
confidence: 83%
See 1 more Smart Citation
“…These metasedimentary rocks are expected to be conductive due to their high content of graphitic metapelites. The fact that the basement is found deeper in our current study area (about 10 km) than in the western part of the district (4 km, see Hübert et al, 2013) is in good alignment with the proposed crustal detachment by Skyttä et al (2013), shown in Figure 1.…”
Section: Large Conductorssupporting
confidence: 83%
“…CTV is located close to magnetic lineaments identified as splays from the Deppis-Näsliden shear zone (DNSZ in Figures 1 and 2), a crustal-scale shear zone stretching in northern Sweden for more than 100 km, most probably cutting the crust deeply. CTV might also be related to the proposed crustal detachment by Skyttä et al (2013) and inferred to follow the dashed line in Figure 1. CTVI would rise to the surface where Bauer et al (2013) propose a south-dipping fault to explain geological field observations and where the airborne magnetics show a change in pattern.…”
mentioning
confidence: 89%
“…Around the same time, a new structural model for the Skellefte-Vargfors groups contact was developed, which led to a geologic model that recognized reactivated synvolcanic faults as primary targets. This was later supplemented by new seismic investigations (Dehghannejad et al, 2010;Bauer, 2013) and further refined in 3D by Skyttä et al (2013). Combining this information with offhole anomalies, an intersection of tremolite marble, subeconomic disseminated pyrite, pyrrhotite, sphalerite, and chalcopyrite, associated with strong sericite and chlorite alteration, gave the first true indication of mineralization at Rävliden North.…”
Section: Brief History Of Discoverymentioning
confidence: 98%
“…The deposits and their host rocks have been subjected to greenschist to lower amphibolite facies metamorphism and polyphase deformation at c. 1.9 to 1.8 Ga during the Svecokarelian orogeny (Skyttä et al, 2020). This has resulted in considerable change in the geometry of ore lenses, including remobilization of primary mineralization (Årebäck et al, 2005;Skyttä et al, 2013).…”
Section: Introductionmentioning
confidence: 99%
“…Bauer et al 2011;Skyttä et al 2013). However, alteration zones in this area have to date only been studied in 2D and on the deposit scale (e.g.…”
Section: Introductionmentioning
confidence: 99%